Why Potassium Is Important for Potatoes - Lakesh K. Sharma; Simranpreet K. Sidhu; Lincoln Zotarelli; Hardeep Singh (EDIS)
This publication focuses on the importance of potassium nutrition for potato (Solanum tuberosum L.) production. This publication aims to detail the relevance of potassium (K) for tuber production, crop demand for this nutrient, recent market trends, and additional information on K management for potato production in Florida. The target audience includes potato growers, Extension agents, crop consultants, representatives of the fertilizer industry, state and local agencies, students, instructors, researchers, and interested Florida residents.